Pengaruh Frekuensi Kunjungan ke Perpustakaan Terhadap Indeks Prestasi Mahasiswa - Ristiani Ristiani (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
As a human being equipped with intellect, it can be understood the importance of libraries in an effort to support the dynamics of academic activities for all elements at IAIN Metro in particular and society in general. Research to be conducted by the authors in this study is a quantitative study. In quantitative research the process of collecting data is done directly or plunged into the field. Based on the results of data analysis conducted, it can be concluded as follows: No significant influence is obtained from the results of chi-square calculated with chi-square table. By using two-party test, we get chi-square table value (x2tabel) at 1% significance level equal to 13,227 and for 5% significance level equal to 9,488. Thus, the calculated chi-square value (x2count) of 0.414 is smaller than the chi-square table at the significance level of 1% and the 5% significance level then Ha is rejected and Ho is accepted.